Lindaman & Ward, History Lessons - How Textbooks From Around The World Portray U.S. History - Mork, Gordon (Teaching History: A Journal of Methods, 2007)
We all recall Robert Burns's couplet, reminding us that we should see ourselves as others see us. Thus Dana Lindaman (a Harvard Ph.D. candidate) and Kyle Ward (a professor of history and politics at Vincennes University) have set a useful task for themselves. History teachers and students of the discipline in general should be interested in reading United States history as seen through others' eyes. But the task is not as straight-forward as it appears. Their study, though a useful and rewarding book, also raises as many questions as it answers.